Dream and Legacy : Dr. Martin Luther King in the Post-Civil Rights Era - Dorsey, William H. L.; Brown, Donathan L.; Clemons, Michael L. (Book collections on Project MUSE., 2017)
"With contributions by: Rosa M. Banda, Michael L. Clemons, Lakeyta M. Bonnette-Bailey, Donathan L. Brown, Hannah Firdyiwek, Alonzo M. Flowers III, Helen Taylor Greene, William G. Jones, Athena M. King, Taj'ullah Sky Lark, Jamela M. Martin, Marcus L. Martin, Byron D'Andra Orey, Amardo Rodriguez, Audrey E. Snyder, James L. Taylor, Leslie U. Walker, and Jason M. Williams This book examines how Martin Luther King's life and work had a profound, if unpredictable, impact on the course of the United States since the civil rights era. A global icon of freedom, justice, and equality, King is recognized worldwide as a beacon in the struggles of peoples seeking to eradicate oppression, entrenched poverty, social deprivation, as well as political and economic disfranchisement. While Dr. King's work and ideas have gained broad traction, some powerful people misappropriate the symbol of King, skewing his legacy. With unique, multidisciplinary works by scholars from around the country, this anthology focuses on contemporary social policies and issues in America. Collectively, these pieces explore wide-ranging issues and contemporary social developments through the lens of Dr. King's perceptions, analysis, and prescriptions. Essayists bring a multidisciplinary and interdisciplinary approach to social policies and current issues in light of his ideals. They strive to glean new approaches and solutions that comport with Dr. King's vision. Organized into three sections, the book focuses on selected issues in contemporary domestic politics and policy, foreign policy and foreign affairs, and social developments that impinge upon African Americans and Americans in general. Essays shed light on Dr. King's perspective related to crime and justice, the right to vote, the hip hop movement, American foreign policy in the Middle East and Africa, healthcare, and other pressing issues. This book infers what Dr. King's response and actions might be on important and problematic contemporary policy and social issues that have arisen in the post-civil rights era."--